Behavioral Economics and Online Donation Behavior on TikTok - Rukiah, Rukiah; Farid, Ahmad Salman (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2025)
The rise of digital philanthropy has transformed the way individuals engage with charitable giving, particularly on social media platforms such as TikTok. Understanding the behavioral economic factors that influence online donation behavior is crucial for optimizing fundraising strategies. This study employs a qualitative research design, incorporating in-depth interviews and content analysis of donation-related campaigns on TikTok. Thematic analysis was conducted to identify key behavioral economic drivers influencing donation decisions. The findings reveal that emotional heuristics, social proof, reciprocity, and frictionless giving significantly impact donation behavior on TikTok. The role of influencers, algorithmic exposure, and real-time donation tracking fosters a community-driven donation culture that encourages both impulse and sustained giving. The discussion highlights how choice architecture and platform design facilitate seamless donation experiences. Social influence mechanisms, such as herd behavior and bandwagon effects, further enhance donation participation. The study suggests that digital fundraising efforts should leverage emotionally engaging content, influencer endorsements, and simplified payment processes to maximize effectiveness. This study contributes to the growing body of knowledge on digital philanthropy by identifying the behavioral economic principles underlying online donations on TikTok. While offering strategic insights for fundraisers, the research acknowledges limitations related to sample demographics and qualitative scope, recommending future studies to explore quantitative metrics, cross-platform donation behaviors, and longitudinal engagement trends. Keywords: Behavioral Economics; Online Donation; TikTok Fundraising; Social Influence; Digital Philanthropy